IMPROVING UNDERSTANDING AND LEARNING OUTCOMES OF STUDENTS GRADE X GB 3 SMK NEGERI 2 TASIKMALAYA ON COMPETENCE ATOMIC STRUCTURE THROUGH THE METHOD OF DISCOVERY GUIDED - Ade Sri Mutiara (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2019)
The background of this research activity is the low interest of students to appreciate the learning of Chemistry subjects, the learning process seems boring, and the students' ability to analyze Chemistry subjects is still low. Research conducted using a qualitative approach, the data is based on obtained from the results of field notes, observations test so that it can be easily understood. To find out the level of understanding of students towards the material being studied, it is done by asking directly to all students whether they are very understanding of the lowest do not understand, students are asked to honestly answer them, and also the test results score data associated with completeness criteria minimal. As for the learning process, Grade X GB 3 students have been grouped and each group have the same task and there are different. In the first cycle, students learn their information through modules. Students actively with friends in their groups learn the material of the atomic structure, which is about determining the number of particles making up the atom, then one of the students in each group presents their findings, then an initial test is held. Because in the first cycle the results were not too satisfying, in the second cycle an additional action was taken in the learning activities, namely where the original method of discovery was only through book literacy, to ensure that the findings were added with digital literacy. In the first cycle the students' activities still showed doubts about their findings and obtained data that was very understanding and understood 13 people or 44.82%, and the remaining 16 people 55.17% lacked understanding and did not understand. while for the mastery of the material carried out through data tests the average is 66.34, and those who reach the minimum completeness criteria score are 13 people or 44.82%. Whereas in the second cycle after it was added with digital literacy to strengthen its findings obtained data that understood very well, and understood 25 people, or 86.20%, and the remaining 4 people or 13.79% said they did not understand and did not understand, while for mastery material that is done through data tests is an average of 80.31, and who have reached the value of completeness criteria there are at least 25 people or 86.20%. Based on the first cycle and second cycle, showed a significant improvement development, therefore the application of guided discovery learning models with the addition of digital media reference sources for chemistry subjects with atomic structure material has proven its success, henceforth the guided discovery learning method would be possibly used as an option to determine the method that will be used in the learning process of any subject.